A Case of Elder Abuse and Undue Influence: Assessment and Treatment From a Geriatric Interdisciplinary Team. (October 2013) - Horning, Sheena M.; Wilkins, Stacy S.; Dhanani, Shawkat; Henriques, Donna
Elder abuse is a pervasive problem that can have lasting emotional and physical consequences, increasing its victims' risk of mortality. Healthcare providers are frequently involved in the detection and intervention of elder abuse. Because of the complexity of these cases, applying treatment interventions within an interdisciplinary care team has been recommended to ensure older adults' safety and welfare. Psychologists in particular are frequently relied upon in these situations because of their expertise in cognitive, psychiatric, and capacity assessment, as well as their ability to intervene in a variety of difficult situations. The following is a report examining the case of Mr. B, who was a victim of elder abuse involving financial exploitation and undue influence. Assessment and treatment interventions were used within the context of an interdisciplinary care team, using a bio-psychosocial approach. A decision-tree model describing the steps to take in assessing and treating financial elder abuse is proposed.